DIFFERENT CONTRIBUTION OF SPECIES AND FUNCTIONAL TRAIT DIVERSITY TO ABOVEGROUND BIOMASS DYNAMICS IN A FOREST LONG-TERM ECOLOGICAL RESEARCH SITE, SOUTH KOREA - J. H. Chun; J. H. Lim; C. B. Lee3 (Journal of Animal and Plant Sciences, 2020)
Understanding the key drivers controlling biomass production in forest ecosystems is an important process from both theoretical and practical perspectives. Here, we examined the relationships of aboveground biomass (AGB) production variables with species diversity, community weighted mean (CWM) values and variety of functional traits during temperate forest succession in a forest long-term ecological research site, South Korea. Our results revealed that species diversity and CWM trait values are crucial drivers for AGB production in a Korean temperate forest. The relative importance of the explanatory variables was different among AGB production variables. Mass ratio mechanism by CWM values of dominant traits was a main driver for initial and last AGBs and the increment of AGB by survivors and recruits, whereas AGB loss by mortality of stems was govern by species diversity. The mechanism governing AGB loss associated with species diversity may relate to size-dependent demographic processes of individual woody stems, especially, the withering of canopy trees. Therefore, our results suggest that mass ratio and size-dependent mechanisms of woody plants may be important drivers shaping the AGB dynamics in our study system.
Keywords: Aboveground biomass; Community weighted mean; Long-term ecological research site; Mass ratio mechanism; Size-dependent demographic process; Species diversity